Meningkatkan Pengalaman Pelanggan di Sektor Kuliner Melalui Augmented Reality pada Menu Digital - Abednego Indra Saputra; Paulus Lucky Tirma Irawan (J-MILE: Journal of Management and Industrial Engineering, 2026)
The development of Augmented Reality (AR) technology has created new opportunities for enhancing interactivity in various industries, including the culinary sector. This study aims to design and develop a mobile application called ARMenu, an interactive digital menu that utilizes AR to display three-dimensional (3D) visualizations of food items. The purpose of this application is to provide restaurant customers with a more immersive and informative experience when selecting meals. The research uses the prototyping development method, allowing iterative feedback from users to refine the system. The application was built using Unity and Vuforia SDK, integrating 3D food models into a mobile interface. Functional and usability testing were conducted with a sample group of 15 Computer Engineering students using the System Usability Scale (SUS). The results show that ARMenu successfully renders food models in AR with realistic visuals and intuitive interaction, achieving an average SUS score of 4.23 out of 5 for ease of use. Users expressed satisfaction with the application's ability to help them visualize food before ordering. The study demonstrates that AR technology can significantly improve customer experience by introducing an innovative way to present menu information through augmented reality in restaurant settings.